Implementasi Algoritma Dijkstra Dalam Pembuatan Aplikasi Pesona Palu - Anshori, Yusuf; Joefrie, Yuri Yudhaswana; Nadyanti, Nadyanti (Fakultas Teknik, Universitas Tadulako, 2018)
This study aims to build application that is able to provide information on the location of culinary tourism, shopping and recreation center for the area of Palu City that runs on the Android platform and able to show the closest path to be traversed in order to help tourists or newcomers who are not too familiar with the city of Palu. Determination of the shortest route in this application using Dijkstra algorithm. This algorithm is used to find the shortest path on a directed graph. This algorithm uses the Greedy principle which states that at each step we choose the minimum-weighted side and put it into the solution set.